CURRENT CHALLENGES IN TRAINING QUALIFIED PROFESSIONALS IN THE FIELD OF PHYSICAL EDUCATION AND SPORTS - Niyazova, Regina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
This article provides a scientific analysis of current aspects of professional training of specialists in the field of physical education in the context of modernizing the modern educational space. The priority of forming comprehensive professional competencies covering pedagogical, methodological, digital, and socio-emotional components of future personnel's professional readiness has been substantiated. Special emphasis is placed on the need to introduce innovative educational technologies, integrate digital resources into the educational process, and develop emotional intelligence and communication skills as key components of the professional development of teachers and coaches. The study also examines contemporary challenges, including the processes of digitalization, globalization, transformation of educational standards, and the evolution of labor market demands.